2022
DOI: 10.1126/sciadv.abn9299
|View full text |Cite
|
Sign up to set email alerts
|

Altered epidermal proliferation, differentiation, and lipid composition: Novel key elements in the vitiligo puzzle

Abstract: Vitiligo is an acquired skin depigmentation disease involving multiple pathogenetic mechanisms, which ultimately direct cytotoxic CD8 + cells to destroy melanocytes. Abnormalities have been described in several cells even in pigmented skin as an expression of a functional inherited defect. Keratinocytes regulate skin homeostasis by the assembly of a proper skin barrier and releasing and responding to cytokines and growth factors. Alterations in epidermal proliferation, differentiation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…Among the various pathogenetic hypotheses, our research has been particularly effective in the explanation of non-immunological factors, demonstrating the presence of metabolic impairment in almost all epidermal cells [ 5 , 7 ]. In accordance with our data, vitiligo could be defined as a mitochondrial disease leading to an aging phenomenon and to an alteration of the skin barrier, which could be an initial event in the development of the inflammatory process [ 5 , 6 , 8 , 38 ]. The regulation of energy metabolism is critical in maintaining intracellular redox equilibrium, strictly related to mitochondria efficiency.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Among the various pathogenetic hypotheses, our research has been particularly effective in the explanation of non-immunological factors, demonstrating the presence of metabolic impairment in almost all epidermal cells [ 5 , 7 ]. In accordance with our data, vitiligo could be defined as a mitochondrial disease leading to an aging phenomenon and to an alteration of the skin barrier, which could be an initial event in the development of the inflammatory process [ 5 , 6 , 8 , 38 ]. The regulation of energy metabolism is critical in maintaining intracellular redox equilibrium, strictly related to mitochondria efficiency.…”
Section: Discussionsupporting
confidence: 87%
“…Accordingly, PGZ reduces the expression of chemokine receptor CXCR3B, decreases the release of several DAMPs as well as, HMGB1 and Hsp70, and significantly lowers the gene expression levels of MICA and MICB. During the last years, our group reported that metabolic abnormalities are common to the entire vitiligo skin [ 7 , 8 ]. Starting from these considerations, we assayed that, in fibroblasts isolated from vitiligo patients, PGZ affected the release of growth factors and improved the production of extracellular components, such as Fibronectin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations